OC-079 Do patients who failed to attend their first bowel cancer screening clinic visit warrant further follow-up?. (23rd September 2015) - Tran, S; Jackson, T; Adams, J; Singh, S; Lipscomb, G R
Abstract : Introduction: The second round of the national bowel cancer screening pilot found that 17% of those with positive faecal occult blood testing did not attend for colonoscopy.1 Some of these individuals may have good reasons for non-attendance (eg, under colonoscopic screening already or electing for private colonoscopy). However, the question remains whether non-attenders harbour the same pathology and need to be pursued. The aim of our study was to assess the incidence of adenomas and cancers in those who did not attend for their first screening clinic visit as part of the Bowel Cancer Screening Programme. Methods: We prospectively collected data from the Bolton screening area between 1 March 2007 and 30 September 2009. The Bolton Screening Centre (BSC) covers a population of approx 800 000 and started screening in Feb 2007. Those who failed to attend their initial clinic visit were sent a second appointment and we identified the proportion where colonoscopy was indicated and the subsequent incidence of adenoma and cancer. Results: One hundred and twenty-four thousand and five individuals were invited for stool testing. 67 420 were returned and 1321 were positive with a subsequent invitation to a bowel cancer screening clinic visit. One hundred and ten patients (8.3%) did not attend their initial appointment. In the early stages of the programme some patients were not offered a second appointment. However, ninety-seven were offered a second appointment. Seventy-eight (80%) attended and 60 went on to colonoscopy. Adenomas were identified in 23 individuals (38% of those investigated) and six patients were found to have colourectal cancer (10%). Two cancers were Dukes A, one was Dukes B and two were Dukes C. One patient was not classified because of his poor general health limiting the indication for staging/surgery. The proportion of patients with colourectal cancer was slightly higher in this group than our overall figures (8.6%) but the proportion of patients with adenomas was slightly lower compared to our overall figures (56%). Conclusion: Although, it might be speculated that non-attenders are self-selecting as those without significant pathology, our data would suggest otherwise. The majority of those offered a second screening visit took up the opportunity. Colonoscopy was indicated in most and the incidence of adenomas and cancer in this group was significant. We conclude that second appointments should be offered to individuals who fail to attend their initial visit as part of the National Bowel Cancer Screening Programme.